The Relationship Between the O Theater Studio and The Tolerance and Self-Confidence of Youth in Angke Village, Tambora District, West Jakarta - Anas Muthtar; Yatimah, Durotul; Darmawan, Daddy (JIV-Jurnal Ilmiah Visi, 2024)
Adolescence is a time when the most important events in human life occur. This period is the formation of their social and professional guidelines, the formation of a worldview, value, motivational and normative sphere. Sanggar Theater O is a community group that exists as an alternative form of transition from negative activities in Angke Village, Tambora District, West Jakarta. The founder of the Sanggar Theater O, Alfian, explained that the birth of the Sanggar Theater O in the RW 03 area was a form of Alfian's desire to be able to create a harmonious environment in the area. Tolerance is a mental attitude that is able to accept other individual differences. Confidence attitudes include the categories of psychological impact of participation in the intervention, physical impact of participation in the intervention, importance of social support, and importance of settings tailored to needs. This research was conducted using quantitative methods. This research was conducted at the Sanggar Theater O, Angke Village, Tambora District, West Jakarta. The research was carried out from 5 to 7 June 2024. The variables in this research included two independent variables consisting of Tolerance (Y1), Self-Confidence (Y2) and one dependent variable Theater Sanggar (X). The population in this study were all members of the Sanggar Theater O, totaling 20 people. The data collection technique uses a questionnaire. The data analysis technique used in this research is descriptive analysis, prerequisite testing. Sanggar Theater O towards tolerance gets a sig correlation value. 0.05 . relationship between Sanggar Theater O get a correlation sig value. 0.05. There is a relationship between Sanggar Theater O towards an attitude of tolerance and there is a relationship between Sanggar Theater O towards an attitude of self-confidence.